Pengembangan Lembar Kerja Peserta Didik Berbasis Riset Pengaruh Getaran Makroseismik Terhadap Perilaku Ikan Lele (Clarias sp.) : (Developing of Student Worksheet Based on Effect of Macroseismic on the Behaviour of Catfish (Clarias sp)) - Muhsinul Ihsan; Afrian Zulkarnaen; Nurdiana Nurdiana (BIODIK, 2022)
Decreasing scientific and proactive behavior caused low motivation and learning outcomes of class XI students of SMA Islam Terpadu Al-Kamal NW West Lombok. The development of Students Worksheets based on research on the effect of macroseismic vibrations on the behavior of Catfish (Clarias sp) is expected to make learning more interactive. This study has three purposes. Firstly,  determining the effect of macroseismic vibrations on the behavior of  Catfish (Clarias sp) followed by determining the feasibility of students' worksheets and its impact on the motivation and learning outcomes. This research consists of two stages, namely observing the behavioral response of Catfish (Clarias sp) to macroseismic vibrations and developing students' worksheets. Four D models which are modified into 3-D were used in developing students' worksheets. The product was validated by two validators and then tested on the students. The collection of motivation data and learning outcomes used questionnaires and tests (pretest-posttest) respectively. Macroseismic vibrations cause stress so that the catfish (Clarias sp) moves to the surface and jumps. The students' worksheets were declared worthy of being tested by the validators. Furthermore, biology teachers and students gave a positive response and stated that the students' worksheets were very good. The average student's motivation increased significantly from 60.38 to 80.88. Likewise, the average of learning outcomes rose significantly from 60.62 to 81.13. Macroseismic vibrations is a stressor that causes abnormal behavior of catfish (Clarias sp). The students' worksheets are stated feasible and very good by validators, biology teachers, and students. The product also raises significantly of student’s motivation and learning outcomes. Key words: students worksheets, students motivation, learning outcomes, earthquake Abstrak  Perilaku ilmiah dan proaktif dalam percobaan yang rendah pada materi sistem koordinasi menyebabkan motivasi dan hasil belajar siswa kelas XI SMA Islam Terpadu Al-Kamal NW di bawah standar. Pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis riset pengaruh getaran makroseismik terhadap perilaku Ikan Lele (Clarias sp) diharapkan membuat pembelajaran lebih interaktif. Tujuan penelitian adalah untuk mengetahui pengaruh getaran makroseismik terhadap perilaku Ikan Lele (Clarias sp), dan kelayakan LKPD serta dampaknya terhadap motivasi dan hasil belajar. Penelitian ini terdiri atas dua tahap yaitu tahapan pengamatan respon perilaku ikan terhadap getaran makroseismik dan riset pengembangan LKPD. Model pengembangan yang digunakan adalah 4-D yang dimodifikasi menjadi 3-D. Produk divalidasi oleh 2 validator kemudian diujicobakan siswa. Pengumpulan data motivasi dan hasil belajar menggunakan angket, lembar observasi, dan tes (pretest-posttest). Getaran makroseismik menyebabkan stres sehingga Ikan Lele (Clarias sp) bergerak menuju permukaan dan melompat. Produk LKPD dinyatakan layak diujicobakan oleh validator. Pendidik dan peserta didik memberikan respon positif dan menyatakan LKPD sangat baik. Rata-rata motivasi belajar siswa meningkat signifikan dari 60,38 menjadi 80,88. Begitu juga dengan rata-rata hasil belajar yang meningkat signifikan dari 60,62 menjadi 81,13. Makroseismik merupakan stresor yang menyebabkan Ikan Lele (Clarias sp) berperilaku abnormal. Produk LKPD berbasis riset perilaku Ikan Lele (Clarias sp) dinyatakan layak dan mendapat respon sangat baik sehingga dapat mampu meningkatkan motivasi serta hasil belajar siswa secara signifikan. Kata kunci: lembar kerja peserta didik, motivasi siswa, hasil belajar, gempa bumi.